Study on the effect of nano and micro MoS2 powder in micro-electrical discharge machining - Prihandana, Gunawan Setia; Sriani, Tutik; Prihandana, Kei; Prihandana, Yuta; Mahardika, Muslim; Abd Shukor, Mohd Hamdi; Mitsui, Kimiyuki (2011)
The application of powder mixed dielectric to improve the efficiency of electrical discharge machining (EDM) has been acknowledged extensively. However, the study of micro-size powder suspension in micro-EDM field is still limited. In this research, nano and micro size powder of MoS2 were used as catalyst agent. Powder suspension in different size was able to provide significant improvement in material removal rate and surface quality to increase the efficiency in mu-EDM processes.